Green sustainable process for chemical and environmental engineering and science : green composites : preparation, properties and allied applications - Altalhi, Tariq; Inamuddin, 1980- (Elsevier, 2022)
Green Sustainable Process for Chemical and Environmental Engineering and Science, the latest release in the Green Composites: Preparation, Properties and Allied Applications series, deals with the most promising aspects of green composites. The book presents in-depth and updated literature related to the manufacturing of green composites and their properties and discusses special features of green composites and their applications in daily life. All green composites covered in this work are polymeric and of bio-origin. The book also provides industrial applications of green composites. Topics covered include the use of green composites, vegetable packing, foam, blends, rubber, solar cells, adhesives and 3D printing.